2013
DOI: 10.5688/ajpe77112
|View full text |Cite
|
Sign up to set email alerts
|

An Oncology Pharmacy Practice Elective Course for Third-Year Pharmacy Students

Abstract: Objective. To develop and implement a 1-credit-hour oncology pharmacy practice elective course for third-year pharmacy students and assess its impact on examination scores in a required pharmacotherapeutics course. Design. Major topics were identified to focus on therapeutic management and supportive care of the oncology patient. Psychosocial topics were incorporated to help pharmacy students better relate to oncology patients. Assessment. Learning was assessed by means of 2 computer-based examinations, weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…A report noting positive reviews by students of an oncology elective and the impact it had on improving grades in their pharmacotherapeutics course has been published previously. 23 Although elective courses in oncology do exist, to our knowledge, our study represents the only published effort that documents the impact of an oncology pharmacy elective course on students' opinions of this career pathway. Our effort to assess opinions before and after the intervention is also somewhat unique, as only a limited number of reports took this important step.…”
Section: Discussionmentioning
confidence: 97%
“…A report noting positive reviews by students of an oncology elective and the impact it had on improving grades in their pharmacotherapeutics course has been published previously. 23 Although elective courses in oncology do exist, to our knowledge, our study represents the only published effort that documents the impact of an oncology pharmacy elective course on students' opinions of this career pathway. Our effort to assess opinions before and after the intervention is also somewhat unique, as only a limited number of reports took this important step.…”
Section: Discussionmentioning
confidence: 97%
“…Also, pharmacists who have completed additional training in psychology are instrumental in helping cancer patients understand and manage long-term psychophysical adverse effects of their anti-cancer medications. Moreover, pharmacists play a crucial role in helping patients with cancer achieve better medication compliance, via interventions, including face-to-face consultations, written materials, and telephone follow-up calls, which significantly improved the patients’ adherence to therapy [ 40 , 41 ].…”
Section: Impact Of Pharmaceutical Care On Adherence To Treatment In Pmentioning
confidence: 99%
“…Several educational initiatives have been implemented to appropriately prepare future practitioners to fulfill this role. 6,[10][11] For example, Plevin and colleagues investigated the role of the pharmacist in providing targeted therapies, and concluded that student pharmacists should be trained in this area to positively affect patient outcomes. 10 Newton and colleagues 6 have suggested that the PharmD curriculum include a combination of didactic courses and practice experiences provided by faculty that include those with a background in oncology practice.…”
Section: Introductionmentioning
confidence: 99%